Сytokine markers for different variants of sclerotic lichen in women - E. V. Kolesnikova; A. V. Zharov; I. A. Kharitonova; Yu. S. Mizina; S. V. Fedak (Медицинская иммунология, 2020)
Our work was aimed for studying the role of systemic of IL-23 and IL-20 levels in different clinical variants of sclerotic lichen in women. The study was based on results of clinical data (anamnesis, examination, palpation, vulvoscopy) and immunological studies (determination of IL-20 and IL-23 cytokines in peripheral blood) in the patients with sclerotic lichen (114 patients aged 42.5±15.1 years). Group I included patients with atrophic variant of sclerotic lichen (n = 58); group II, with sclerotic variant of sclerotic lichen (n = 34). Group III included women with a sclero-atrophic variant of this disorder (n = 22). The control group consisted of conditionally healthy women without present, or previously documented vulvar pathology (30 persons). Criteria for inclusion were as follows: women 20 to 60 years old, the presence of a benign vulvar disease, absence of treatment with immunotropic drugs over past year. Exclusion criteria: presence of viral infection (HPV, HSV), detection of STI, presence of acute inflammatory process (including vulvitis and vaginitis), cancer diagnosis, symptoms of autoimmune disorders, pregnancy, and the patient’s reluctance to participate in the study.Predominant increase of IL-23 was revealed in all clinical groups of the examined patients, the most pronounced increase (2.7 times) was in severe sclerotic lichen (p < 0.0001). IL-23 concentration in the 2nd clinical group corresponded to the reference age-matched values. There was a significant increase in the blood content of IL-20 in subgroup 2.2 of the patients with sclerotic lichen (p < 0.0001), as well as in patients from group 3 with a mixed clinical course of its disorder (p < 0.0001). Meanwhile, the absence of pronounced vulvar tissue sclerosis in sclerotic variant of sclerotic lichen (subgroup 2.1) was accompanied only by a tendency for increased IL-20 concentration (p = 0.502), and only a trend for decrease in atrophic variant of sclerotic lichen (p = 0.288). In general, analysis of these data presumes a significant role of IL-20 and IL-23 in pathogenesis of sclerotic lichen in women. The cytokine assays in various clinical variants of this vulvar disorder may provide additional differential diagnostics (IL-20), and to assess severity of atrophic and sclerotic changes in vulvar tissues (IL-23) in women with sclerotic lichen.